Evaluation of teaching in pandemic times: Student opinions at three Mexican public universities - Henriquez, Patricio; López, Galo; Camacho, Noelia; Hurtado, Sara (Education Policy Analysis Archives, 2022)
The study aims to analyze the opinion of students at three Mexican public universities about the performance of their teachers in the framework of the virtual modality required by the COVID-19 pandemic. Since the declaration of the global pandemic situation, all educational levels worked remotely in an urgent, improvised and, in many cases, unplanned manner. This study considers dimensions associated with teaching planning, methodologies and work dynamics, teaching and learning strategies, along with learning assessment during the 2020-2022 period. The results show that most of the teachers continued to work under synchronous class dynamics, and that they had little preparation or knowledge in the elaboration of instructional designs for distance education, perpetuating traditional educational models focused mainly on the transmission of contents. It is noteworthy that the majority of the students gave a positive opinion about the work modalities favored by their teachers. Regarding their evaluation of learning, a positive opinion of the students was observed: they felt comfortable with these strategies, they considered that their own learning was promoted and improved, stating that their teachers recreated real and authentic situations to evaluate the contents.